Perencanaan Strategis SI/TI di SMA YPK Diaspora Menggunakan Ward and Peppard - Jessica Nathania Kho; Agustinus Fritz Wijaya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
In this digital era, education needs to adapt and use IT' advantage to innovate and not to be left behind. One of the private high schools in Jayapura City that uses IS/IT to support business processes is SMA YPK Diaspora. They haven't fully implemented the integrated IS in managing the school. They applied IS only in a few divisions and aren't yet fully effective. The research purpose is to create strategic planning of IS in supporting the IS/IT application. The key in implementing IS/IT is strategic planning which isn't just a school strategy but needs to be integrated with IS/IT strategic planning that is in line with the technology needs in every activity. This study uses the Ward and Peppard method and several analytical tools, namely Value Chain Analysis, SWOT Analysis, PEST Analysis, Porter's Five Force Model Analysis, and McFarlan Strategic Grid Analysis. This research includes several recommendations, namely IS/IT application portfolio recommendations, suggestions for upgrading existing IS, establishing an IS/IT division, and performing IS/IT infrastructure maintenance. Recommendations for IS/IT application portfolio are School SIM, E-Raport, E-Library, IS Library, and IS Alumni. The implementation of IS is recommended in stages over four years and adjusted to the conditions of SMA YPK Diaspora.